2014
DOI: 10.1111/nuf.12058
|View full text |Cite
|
Sign up to set email alerts
|

Do Higher Dispositions for Empathy Predispose Males Toward Careers in Nursing? A Descriptive Correlational Design

Abstract: Empathy plays a significant role in attracting men to a nursing career. Male nurses are not only caring individuals but also have high problem-solving skills in complex environments, demonstrating their strong systemizing characteristics to organize, plan, and implement care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
2
18
2
2
Order By: Relevance
“…Although this study did not use the JSE-HP-S, their observed improvement in empathy levels, and that females improve the most is consistent with our findings. In contrast, it should be noted that there are reported studies where a gender difference is not observed [43][44][45][46], and warnings that this has little real-life applicability [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not use the JSE-HP-S, their observed improvement in empathy levels, and that females improve the most is consistent with our findings. In contrast, it should be noted that there are reported studies where a gender difference is not observed [43][44][45][46], and warnings that this has little real-life applicability [39].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, men and women with higher levels of empathy are more likely to be drawn to people-orientation subject majors (e.g., nursing [Penprase, Oakley, Ternes, & Driscoll, 2014]). Further research is needed to unpack these effects over time to determine directions of effects, however.…”
Section: Discussionmentioning
confidence: 99%
“…The place of gender in the development of empathy has been examined by Penprase, Oakley, Ternes, and Driscoll (2012). In a study of 1,482 non-nursing students and 392 nursing students, female students achieved higher empathy scores than male students.…”
Section: Introductionmentioning
confidence: 99%